Disputas pela (des)estabilização do regime cisheteronormativo na Educação Física escolar - Silva Santos, Ana Paula da (Educación Física y Ciencia.)
As an excerpt from an action research that tensioned gender issues in Physical Education classes, we seek, in this article, to problematize how boys and girls enunciate meanings of reproduction and destabilization of the cisheteronormative regime present in the pedagogical practices of Physical Education at school. For this, we propose the interlocution of post-structuralist gender and feminist studies with a critical intercultural perspective by authors such as Judith Butler, Juliana Jardim, Vera Candau and Marcos Neira, and operationalized two discussion groups, according to Wivian's Weller proposal, at the beginning and at the end of the research, with boys and girls who are students of elementary school. Among the results, the subjects' speeches stated different affects of cisheteronormativity in school Physical Education practices, either by the fixed positions for male and female in classes, mainly at the beginning of the research, as well as the destabilization of these senses, by new looks, new ideas and new thoughts in relation to gender norms in classes, which have been reframed with the development of research.